Preparation of 99mTc-Kanamycin Using a Direct Labeling Method - E.M. Widyasari; M.E. Sriyani; T.H.A. Wibawa; W. Nuraeni (Atom Indonesia, 2015)
Infectious diseases are still the leading cause of death in the world.  The accurate technique for early detection and determination of the exact location of infection in the body is still needed. Nuclear techniques are capable for this purpose while other techniques such as MRI, USG and CT-SCAN sometimes cannot be applied. 99mTc-kanamycin radiopharmaceutical is complex of kanamycin and technetium-99m radionuclide, was used for bacterial detection of infection. The labeling studies of 99mTc-kanamycin has been carried out by the indirect labeling method using pyrophosphate as a co-ligand with the results of labeling efficiency above 95%. However, the presence of radiochemical impurities in the form of 99mTc-pyrophosphate in the indirect labeling have to be considered which may interfere the imaging result. This study aimed to determine the optimum labeling conditions of 99mTc-kanamycin by direct labeling method. Kanamycin was successfully labeled with technetium-99m through direct labeling method. The labeling efficiency was determined by ascending paper chromatography using Whatman 3 paper  as the stationary phase, and acetone as the mobile phase to separate the radiochemical impurities in the form of 99mTc-pertechnetate. While impurities in the form of 99mTc-reduced  were separated using the stationary phase ITLC-SG and 0.5 N NaOH as mobile phase. The experiment result showed that the optimum labeling conditions obtained by using 5 mg kanamycin, 30 µg SnCl2.2H2O, and pH of labeling was 9. The incubation time of labeling was 30 min at room temperature, provided labeling efficiency of 92.31 ± 1.74 %.The successful of kanamycin labeling with high efficiency makes 99mTc-kanamycin can potentially be used as a radiopharmaceutical for the early detection of infectious diseasesReceived: 04 October 2014; Revised: 28 June 2015; Accepted: 11 August 2015